2020
DOI: 10.1016/j.ijmultiphaseflow.2020.103233
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of homogeneous and isotropic turbulence by sub-Kolmogorov particles: Impact of particle field heterogeneity

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…However, the proposed modeled LES considers each effect (i.e., the increased particle dissipation and the reduced fluid dissipation) separately and does not rely on compensation of errors. It is known from the literature that for Stokes numbers that are not significantly smaller than one, the total dissipation in a particle-laden flow is increased [19][20][21]23], which also applies to the Stokes numbers investigated in the present study. The total dissipation has contributions from the particles and the fluid, as it occurs in a single-phase flow.…”
Section: B Two-way Coupled Configurationssupporting
confidence: 71%
See 2 more Smart Citations
“…However, the proposed modeled LES considers each effect (i.e., the increased particle dissipation and the reduced fluid dissipation) separately and does not rely on compensation of errors. It is known from the literature that for Stokes numbers that are not significantly smaller than one, the total dissipation in a particle-laden flow is increased [19][20][21]23], which also applies to the Stokes numbers investigated in the present study. The total dissipation has contributions from the particles and the fluid, as it occurs in a single-phase flow.…”
Section: B Two-way Coupled Configurationssupporting
confidence: 71%
“…Extensive research has been carried out to better understand the modulation of turbulence by particles. Studies of forced and decaying homogeneous isotropic turbulence (HIT) have shown that the presence of particles can modify the total dissipation in two ways [19][20][21][22][23]:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysing the turbulent energy spectrum in two-way coupling suggested that particles attenuate energy at low wavenumbers and augment it at high wavenumbers (Letournel et al. 2020), and this effect enhances with the rise in particle number density (Hassaini & Coletti 2022). The increase in small-scale energy escalates , the rate of energy transfer from the large to small scales, growth rate, and drops (Elghobashi & Truesdell 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The Large Eddy simulation (LES) is widely used to understand and predict turbulent particleladen flows. The most classical way consists in combining a single-phase LES model to describe the gas phase, with a LES model for the particulate phase.The objective of a LES particle model is to recover the DNS statistics and macroscopic trends, such as two-way coupling between the spray and the gas phase [1]. Indeed, the retro-coupling can occur at small scales of the flow, and the LES simulation affects not only the particle phase field, but also the one of the carrier phase because of the missing interactions at small scales of the flow with particles.…”
Section: Introductionmentioning
confidence: 99%